The Influence Of Word Of Mouth Communication, Packaging Design, And Brand Image On The Buying Interest Of King Consumers Of Arjuna Cheese Banana, Surabaya - Kezia Conchita (Journal of World Conference (JWC), 2019)
This study aims to determine the effect of word of mout communication, packaging design, and brand image on the buying interest of king consumers of arjuna cheese banana in Surabaya. this research is a type of quantitative research. The population of this study is the king consumer arjuna surbaya cheese banana using accidental sampling technique. This study used a questionnaire with a total of 100 respondents. this analysis technique is multiple linear regression analysis using SPSS version 18. the results of this study indicate that word of mouth communication, packaging design, and brand image have a significant effect on buying interest